2022
DOI: 10.3389/fpubh.2022.1054615
|View full text |Cite
|
Sign up to set email alerts
|

Living alone is associated with a higher prevalence of psychiatric morbidity in a population-based cross-sectional study

Abstract: BackgroundLiving alone has been linked to poor mental health, however large-scale epidemiological studies on the association between living alone and psychiatric morbidity including depression and anxiety are lacking. The aim of this study was to investigate this issue in a large Taiwanese cohort.MethodsIn this cross-sectional study, we enrolled 121,601 volunteers from 29 community recruitment stations in Taiwan and divided them into two groups based on whether or not they lived alone. Psychiatric morbidity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 75 publications
1
4
0
Order By: Relevance
“…However, the association between living alone and psychiatric morbidity was significant in married subjects, but not in unmarried subjects. This study ( 9 ) evaluated only the presence or absence of living alone for household size, failed to conduct stratified analyses by gender, and did not use a randomly selected population, which may have contradicted our findings. Protective effects of living with a partner on mental health are considered to be that people living with a partner, whether married or in a common law relationship, may receive social and psychological support from their partners and that sharing financial resources reduces the stress associated with financial problems ( 38 ).…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…However, the association between living alone and psychiatric morbidity was significant in married subjects, but not in unmarried subjects. This study ( 9 ) evaluated only the presence or absence of living alone for household size, failed to conduct stratified analyses by gender, and did not use a randomly selected population, which may have contradicted our findings. Protective effects of living with a partner on mental health are considered to be that people living with a partner, whether married or in a common law relationship, may receive social and psychological support from their partners and that sharing financial resources reduces the stress associated with financial problems ( 38 ).…”
Section: Discussionmentioning
confidence: 59%
“…In this study, a stratified analysis by gender and marital status showed a dose–response relationship between household size and SPD in never-married persons, regardless of gender. According to a large-scale population-based study consisting of cancer-free volunteers aged 30–70 years in Taiwan ( 9 ), the prevalence of psychiatric morbidity was significantly higher among those living alone than among those living with their families. However, the association between living alone and psychiatric morbidity was significant in married subjects, but not in unmarried subjects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations